1997
DOI: 10.1152/ajpregu.1997.272.6.r1990
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of glucocorticoids in mediating endotoxin-induced changes in IGF-I and IGFBP-1

Abstract: The purpose of the present study was to determine whether endogenous elevations in glucocorticoids mediate the changes in insulin-like growth factor (IGF) 1 and IGF binding protein (IGFBP) 1 levels in plasma and tissues observed after in vivo administration of lipopolysaccharide (LPS). In overnight-fasted male rats LPS injected via the tail vein decreased the IGF-I concentration in plasma, liver, and skeletal muscle (30-45%) and increased IGF-I content in kidney (approximately 3-fold). LPS also decreased IGF-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 0 publications
5
39
2
Order By: Relevance
“…Furthermore, this glucocorticoid was able to prevent the decrease in renal IGF-I mRNA caused by LPS. These results contrast with others previously reported (Li et al 1997), in which the LPS-induced decrease in hepatic IGF-I gene expression and the increase in renal IGF-I gene expression were attenuated by pretreatment with the antiglucocorticoid RU-486. However, in this study, the antagonistic action of RU-486 was not effective enough, since it did not increase corticosterone levels in rats treated with LPS.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this glucocorticoid was able to prevent the decrease in renal IGF-I mRNA caused by LPS. These results contrast with others previously reported (Li et al 1997), in which the LPS-induced decrease in hepatic IGF-I gene expression and the increase in renal IGF-I gene expression were attenuated by pretreatment with the antiglucocorticoid RU-486. However, in this study, the antagonistic action of RU-486 was not effective enough, since it did not increase corticosterone levels in rats treated with LPS.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, with doses of LPS lower than those used in the present study (Priego et al 2003a) or in arthritic rats (López-Calderón et al 2001) we found a decrease in hepatic IGF-I mRNA without changes in the GH receptor. Li et al (1997) reported that LPS increased renal IGF-I mRNA. Discrepancies with our findings could be due to liver and kidney IGF-I mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RU486 has a high affinity for cytosolic type II glucocorticoid receptors in various target tissues and exhibits little agonist activity (40). The dose of RU486 used in the present study has been shown to attenuate glucocorticoid-induced increases in catabolism and ameliorate endotoxin-or cytokine-induced changes in the IGF system and muscle protein balance (14,39,60).…”
Section: Methodsmentioning
confidence: 90%
“…The catabolic insults of LPS and sepsis produce a rapid and sustained elevation in the circulating concentration of glucocorticoids (13,39), and glucocorticoids have been generally reported to reduce IGFBP-5 mRNA under in vitro conditions (8,49). To examine the role of glucocorticoids, initial in vitro studies were performed by treating C 2 C 12 myocytes with dexamethasone.…”
Section: Lps-and Sepsis-induced Changes In Gastrocnemius Igfbp-5mentioning
confidence: 99%